Remittances, finance and growth: does financial development foster remittances and their impact on economic growth - Izabela Sobiech (FIW - Research Centre International Economics, 2015)
In this paper, I measure the importance of remittances and financial development for developing countries. I estimate an index of overall financial conditions and use it to determine the relevance of the financial sector as a transmission channel for remittances to affect economic growth. The index brings together information from existing measures, reflecting size, depth and efficiency of the financial sector. It is created by means of an unobserved components model. I show that the more financial development in a country, the smaller becomes the impact of remittances on economic growth and it can even turn negative. For countries with weaker financial markets there is a positive effect, but significant only at the earliest stages of financial development. The effect becomes negative in the third quartile of financial development. These results hold irrespective of the measure of financial development included, but are most profound in case of the created index. This means that estimates based on proxies might be slightly biased. I also show that countries with both low levels of remittances and financial development should first focus on developing the latter, while migrants' transfers become important for growth if the country has a moderate level of financial development.
Keywords: F24; O11; O15; O16; 330; remittances; economic growth; financial development; unobserved components model; dynamic panel data analysis